Faktor Yang Berpengaruh Terhadap Kinerja Guru Pada Sekolah Menengah Di Kota Batam - Dame Afrina Sihombing* (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2020)
ABSTRACTEducation in Indonesia is increasingly worrisome. The ranking is done in ASEAN through the Education Index by Human Development Reports, where Indonesia is on 7th position with a score of 0.62. In addition, data from the Global Talent Competitiveness Index (GTCI) in 2019 said that in the 67th order out of 125, HR in Indonesia did not have good competitiveness compared to other countries. The population of this research is secondary school teachers in Batam City. 375 questionnaires were distributed to secondary schools in Batam City. This research was tested using SPSS. The results of this study indicate that motivation, satisfaction, attitude and performance of knowledge management have a significant effect on performance, while social support has no influence on performance. This is because most teachers rarely meet other people outside the scope of the school so this situation is considered to be monotonous because they only teach and they become less in establishing relationships with people outside their scope.Keywords: Motivation, Social Support, Satisfaction,Attitude, Performance